Transformasi Digital di Pembangkit Listrik di Indonesia: Kajian dari Sisi SDM dan Teknologi - Paryanto, P; Indrawan, Harry; Cahyo, Nur; Aisyah, Siti; Suprihanto, Agus; Sulardjaka, S (ROTASI, 2021)
In 2021, several power plants in Indonesia have been started a digital transformation to increase efficiency and reduce operating costs. Therefore, in order to accelerate and ensure the sustainability of the transformation, it is necessary to analysis the readiness of human capital and its technology/systems. In this research, methods that are used are: survey, discussion, and verification of several power plants in Indonesia regarding their readiness and conditions. The result of the study shows that its need to increase digital competencies and open mindset of existing employees at the power plant, both at operator and management level. The digital transformation of Indonesian power plants requires an upskilling program for the employee, which is needed to create appropriate digital innovation and accelerate the digitization project. Otherwise, in terms of technology, it needs to increase cybersecurity, useability, and interoperability of the digital technologies. Although cyber security in power plants is sufficient, it needs to standardize the OT/IT connection. Â Â